Using Computer-Assisted Teaching to Promote Constructivist Practices in Teacher Education - Nix, Rebekah; Fraser, Barry (Nova Science Publishers Inc., 2011)
In this chapter, we report how the incorporation of information and communications technology (ICT) into a teacher professional development program fostered constructivist teaching/learning practices in school classrooms. Changing the teachers' learning environment at the university level, based partly on computer-assisted teaching, fostered similar changes in their students’ middle-school learning environments. The Constructivist Learning Environment Survey (CLES), which provided a critical scaffold for design and delivery, was administered to 845 students to 17 teachers. When compared to other classrooms within the same middle schools, these science classrooms were perceived to be significantly more positive in terms of the CLES scales of Personal Relevance, Shared Control, Critical Voice, and Student Negotiation. Qualitative data from observations and in-depth case studies provided further insight into the ways in which the ICT-enhanced program changed the classroom practice of experienced science teachers. Four assertions regarding the implementation of constructivism were identified relating to teacher collaboration, efficacy, understanding, and facility.